Attitudes of English Teachers towards Distance Learning programs in the Karak Kasabah Directorate of Education - Alja'afreh, Hanan Mohammad AbdAlkareem (Journal of Educational and Psychological Sciences, 2020)
This study aimed to identify the attitude of English teachers toward distance learning programs in the Karak Kasabah Directorate of Education study sample consisted of (160) male and female teachers. To achieve the objectives of the study, a questionnaire was used as a tool for data collection; it consisted of (27) paragraphs. The result showed that the attitude of English teachers toward distance learning programs was positive with (3.92) score The finding also showed there were no statistically significant differences between attitude refers to the sex (male and female) of teachers in addition there were statistically significant differences between teachers (5years and less) of experience and with (5-10) years of experience in favor of the second group and statistically significant differences between teachers (5-10) years of experience with (10 and more) years of experience in favor of the second group. Based on the results, the researcher presented a set of recommendations and proposals to enhance the attitudes of English language teachers towards distance learning programs in the Directorate of Education in the Karak Kasbah and throughout the Kingdom of Jordan.
Keywords: Distance Learning; Attitudes; English Teachers